Lecture notes on composite materials current topics and achievements - Borst, Rene de; Sadowski, Tomasz 1954- (New York Springer, 2008)
This text explores new developments in the modeling of composite materials. It fully covers multiscale concepts and other developments such as coupling stress analysis and diffusion phenomena that arise from hygral and/or thermal loading.
Electronic reproduction.
Keywords: Composite materials; Electronic books